2020
DOI: 10.1136/esmoopen-2020-000829
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer subtypes: implications for the treatment and survival of patients in Africa—a prospective cohort study from Mozambique

Abstract: BackgroundData regarding breast cancer epidemiology, treatment and survival in Africa are scarce. We aimed to assess the distribution of breast cancer subtypes in Mozambique and its impact on patients’ treatment and survival. The concordance of biomarker assessment between cytological and histological samples was also evaluated.MethodsProspective cohort study including 210 patients diagnosed between January 2015 and August 2017, followed to November 2019. Clinicopathological characteristics, treatment, 3-year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…We conducted the prospective Moza-BC cohort study, which included consecutive patients with newly diagnosed breast cancer with a pathological diagnosis between January 2015 and August 2017 (supplemental online Fig. 1) [26]. Data on socio-demographic characteristics, risk factors, HIV status, clinical and tumor characteristics, treatment, and survival of patients treated in the oncology unit of the © 2020 AlphaMed Press Survival Impact of a Multidisciplinary Tumor Board Maputo Central Hospital were prospectively collected until July 2018.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…We conducted the prospective Moza-BC cohort study, which included consecutive patients with newly diagnosed breast cancer with a pathological diagnosis between January 2015 and August 2017 (supplemental online Fig. 1) [26]. Data on socio-demographic characteristics, risk factors, HIV status, clinical and tumor characteristics, treatment, and survival of patients treated in the oncology unit of the © 2020 AlphaMed Press Survival Impact of a Multidisciplinary Tumor Board Maputo Central Hospital were prospectively collected until July 2018.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Likewise, we have no information on breast cancer family history among the controls, but as the proportion of cases with a positive family history was very low (4%), this may be of little relevance within this population. Around 25% of the cases were HIV-positive (27), but this information was not available for controls. Yet, although some U.S. studies have reported a lower incidence of breast cancer among women with HIV infection compared with the general population (64), African studies show no effect of HIV on breast cancer risk (65,66).…”
Section: Discussionmentioning
confidence: 99%
“…Still, an absence of effect in HR-negative tumors could be explained by the high adherence to breastfeeding among Mozambican women, which reinforces the need to promote this behavior-especially since the proportion of women with HR-negative and TNBC is already high in Mozambique (33% and 25%, respectively; ref. 27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations